Analisis Ketersediaan Kadmium di Tanah dan Beras Yang Berasal dari Desa Detusoko Barat - Charly Mutiara; Iswawan Redu; Josina Irene Brigetha Hutubessy (Agriculture Faculty of Flores University, 2020)
Cadmium is a heavy metal that is widely found in agricultural land because of the frequent use of inorganic phosphorus fertilizers. The use of high phosphorus inorganic fertilizers is also used by farmers who cultivate rice in Detusoko Barat Village. Therefore, research has been carried out with the aim of knowing the cadmium content in paddy soil and rice and its comparison with the minimum limit of cadmium in rice and soil. This research is survey research, in which the determination of soil and rice samples using a purposive sampling method. From this method, the soil samples taken are rice fields cultivating Palembang, Bengawan and Kental rice varieties. And the rice samples taken were rice from the three varieties. The variables observed were cadmium from the soil and rice and soil pH. The results showed that the cadmium content in Palembang rice soil was 0.015 ppm, Bengawan 0.006 ppm, and thick 0.001 ppm, while the results of the research on cadmium content in Palembang rice were 0.007 ppm, Bengawan rice was 0.008 ppm, and thick rice was 0.006 ppm. Where the cadmium content in rice is still below the minimum limit that has been set.